Development of electrode materials for flexible potassium-ion batteries. (1st June 2023) - Li, Zongyou; Gao, Yanjun; Huang, Hanjiao; Wang, Wei; Zhang, Jianguo; Yu, Qiyao
Abstract: Wearable smart devices have gradually become the development trend, and it calls for functionalized flexible batteries. The development of suitable electrode materials is one of the key parts to meet the electrochemical requirements, as well as light weight, good mechanical properties and high energy density. However, severer volume expansion occurs after repeated intercalation/deintercalation of large-radius K ions, making the development of flexible potassium-ion batteries (PIBs) more challenging. To realize low-cost, high-safety and more practical flexible PIBs, more efforts are needed in the exploration of electrode materials. In this review, we summarize the research progress of all the reported flexible PIBs till now, focus on the research results of flexible electrode materials with different dimensions in the aspects of structural design, manufacturing process and electrochemical performance. Finally, we analyze and discuss the key challenges faced by flexible electrode materials of PIBs, and provide the prospects to the practical use of low-cost flexible PIBs in smart devices. Graphical abstract: Image 1 Highlights: The research progress of all the reported electrode materials for flexible PIBs is summarized. The electrode materials are analyzed in terms of structural design, manufacturing process and battery performance. Challenges and strategies for the practical use of low-cost flexible PIBs are presented.